Effect of Acceptance and Commitment Therapy on Depression and Quality of Life among Women with Chronic Pain during COVID-19 Pandemic Lockdown - Mohamad Reza Sobhani; Sara Jahandar Pour; Nasrin Khalili (Golestan University Of Medical Sciences, 2022)
Background and objectives: The coronavirus disease 2019 (COVID-19) pandemic is one of the most important healthcare and social challenges. The aim of this study was to evaluate the effect of acceptance and commitment therapy (ACT) on depression and quality of life among women with chronic pain during the COVID-19 pandemic lockdown. Methods: This study had a quasi-experimental pretest-posttest design with a control group. The study included 35 women with chronic pain who were randomly divided into an experimental group (n=18) and a control group (n=17). The experimental group received six sessions of weekly treatment based on the ACT matrix. All participants completed the Beck Depression Inventory (BDI-ΙΙ) and the World Health Organization Quality of Life Questionnaire (WHOQOL-BREF) in pretest and posttest. Collected data were analyzed with SPSS (version 23) using descriptive statistics (mean and standard deviation), analysis of covariance (ANCOVA), independent t-test, and the Levene's test. A p-value less than 0.05 was considered statistically significant. Results:  The weekly ACT treatment significantly reduced depression (F=8.72, p=0.01) and significantly increased quality of life (F=11.24, p=0.01). Conclusion: Group psychotherapy based on the ACT matrix can significantly reduce depression and increase quality of life among women with chronic pain during the COVID-19 pandemic lockdown.